Acceptance of Colonoscopy Requires more than Test Tolerance - Amanda Condon; Lesley Graff; Lawrence Elliot; Alexandra Ilnyckyj (Canadian Journal of Gastroenterology)
BACKGROUND: Colon cancer screening, including colonoscopy, lags behind other forms of cancer screening for participation rates. The intrinsic nature of the endoscopic procedure may be an important barrier that limits patients from finding this test acceptable and affects willingness to undergo screening. With colon cancer screening programs emerging in Canada, test characteristics and their impact on acceptance warrant consideration.